2016
DOI: 10.1080/00405000.2016.1192236
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recycled fibers on the washing performance of denim fabrics

Abstract: In this study, denim fabrics were produced with yarns obtained from cotton fibers (CO), recycled cotton fibers obtained from yarn wastes (r-CO), and fibers produced from recycled PET bottles (r-PET). Enzyme and stone washing processes were applied systematically on these fabrics. Mass per unit area, breaking force, elongation at max force, tear strength, air permeability, and circular bending rigidity of fabrics were measured. The findings showed that r-CO fiber has negative effect on tear and breaking force. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Among different processing involved in denim garments manufacturing, washing process is considered as one of the important process parameters [30].…”
Section: Introductionmentioning
confidence: 99%
“…Among different processing involved in denim garments manufacturing, washing process is considered as one of the important process parameters [30].…”
Section: Introductionmentioning
confidence: 99%
“…Denim products have been widely recognized to significantly influence consumers' way of entity since they were invented [9,10]. Denim also has changed its appearance from traditional work-wear to casual clothing to the first wear and functional consumption [11,12]. In reality, Denim is a stiff and gloomy blue element without even any mode of attraction but washing is the groundbreaking mechanism that has transformed the global denim illustration [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[19]. Most of the recycled PET flakes produced worldwide are utilized for staple fiber applications in textile sector ( Figure 2) [8,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that knitted fabrics including virgin PET had better performance specifications than that of r-PET. According to the test results, they offered to use blends of r-PET fibers in suitable proportions according to usage area in order to prevent the decrease in fabric performance instead of using virgin PET fiber [19].…”
Section: Introductionmentioning
confidence: 99%